AUTOMATED PRODUCTION SYSTEMS CAD / CAE / CAM - Rojas Lazo, Oswaldo (1999)
This paper presents the results of research conducted by the authors on the subject and proposed the creation of an automated production lab with three distinct areas: Apparel, Footwear and CNC.